Short Communication: Morphological characterizations of Aphis passeriniana (Del Guercio) (Hemiptera: Aphididae) living on common sage in Turkey - AGUSTİN ZARKANİ; FERİT TURANLI (Society for Indonesian Biodiversity, 2018)
Zarkani A, Turanl? F. 2018. Short Communication: Morphological characterizations of Aphis passeriniana (Del Guercio) (Hemiptera: Aphididae) living on common sage in Turkey. Biodiversitas 19: 1319-1325. Aphis passeriniana (Del Guercio) (Hemiptera: Aphididae) living on sage plant in Turkey is already recorded, but some morphological characterizations are still needed to extend. Here, morphometrics data of A. passeriniana is described from apterous viviparous females (fundatrigeniae and fundatrices) attacking Salvia officinalis Linnaeus (Lamiaceae) in Turkey. Seventy specimens were collected in Izmir province between January 2015 and December 2017. The study revealed that apterous viviparous females of A. passeriniana turkish species have body lenght of 0.715-1.407 mm, rostal segment IV+V of 1.80-2.49 × hind tibia II, antennae processus terminalis/base of 1.4-1.8, siphunculus of 0.56-1.56 × cauda length and cauda of 3-6 setae. Biometric data of alate viviparous and intermediate individual between apterous and oviparous, and also a revision of identification key for the species within aphid species in Salvia are consisted.